Venturing Oil Fund Policy Globally - Veggeland, Noralv (Horyzonty Polityki, 2018)
RESEARCH OBJECTIVE: The systematic global market risk of the type found in the gigantic Norwegian Oil Fund, called “Government Pension Fund – Global (GPF-G),” is discussed at length in this study. The objective is to find out if the risk capital animate ethical venture initiative. In the financial and entrepreneurial literature it has over time become common to relate systematic vulnerability and risk to a long range of factors that might cause imbalance and failure. THE RESEARCH PROBLEM AND METHODS: It is by scholars postulated that risks today related to innovations and unethical and uncontrolled venture capital have a different significance for everyday life from the risks that applied to previous historical eras. It claims that human activity, innovation and technology in advanced political and economic modernity produce as a side-effect risks venturing investment. That demands specialised expertise to access and recognize, and are collective, global, and irreversible in their impact. THE PROCESS OF ARGUMENTATION: To abstain from venturing actions are a way out of the dilemma for the investors. The Norwegian petroleum activity under regulatory management and control is an example of that. The Fund’s revenues have been shrinking lately following the oil prices of the market diving down globally. Perhaps the Norwegian Oil Fund, it is argued, ought to be restructured in a framework of ethics to become less risk exposed in a global financial market perspective, and become more innovative and ethical directed. RESEARCH RESULT: The Norwegian government first transferred capital to the fund in May 1996. By the end of the second quarter of 2017, the fund had received a total of 3,360 billion NOK and amassed a cumulative return of 3,622 billion NOK. The fund generated an annual return of 5.9 percent between 1 January 1998 and the end of the second quarter of 2017. After management costs and inflation, the annual return was 4.0 percent. Norway is invested its oil capital savings mainly in European and U.S. financial markets. In the Norwegian debate on the Oil Fund policy it has also been proposed that the management of the Fund should focus on investments for helping forward entrepreneurship, economic growth and poverty alleviation in developing countries, and ethical management in general. CONCLUSIONS, INNOVATION AND RECOMMENDATIONS: Ethical management of the Norwegian Oil Fund could be exercised in two different manners; by negative exclusion or positive selection. For some years now, in the public debate, it has been recommended that the ethical management should be reoriented from negative screening to innovative positive selection. Instead of excluding companies that violate the decided ethical standards, one should invest only in companies and branches that appear to be, in some sense, an active force for the good on ethical issues.